Awareness of occupational hazards in learning organizations: Knowledge sharing behavior and sense of spirituality perspective. Issue 1 (4th February 2019) - Rahman, Muhammad Sabbir; Mannan, Mahafuz; Hossain, Md. Afnan; Gani, AAhad M. Osman
Abstract : Purpose: The purpose of this research is to investigate the significant antecedents that influence students' awareness of occupational hazards (AOHs) in their respective institutions. The researchers proposed a theoretical model consisting of three dimensions: knowledge sharing behavior (KSB), sense of spirituality (SS) and awareness of occupational hazards (AOHs). Design/methodology/approach: This study targets students of different public and private higher learning institutions in Bangladesh with a total of 260 respondents, utilizing a survey questionnaire as the data collection instrument to test the proposed conceptual model. The structural equation modeling approach was used to test the proposed model. Findings: The results show that SS has a mediating effect on KSB and AOHs at higher learning institutions. Originality/value: The study contributes for first time to the theoretical novelty of the body of the existing literature in the domains of students' KSB, SS and AOHs. The study also provides insight on future research directions by helping in identifying gaps in literature in this field and higher learning institutions in Bangladesh.